RISK ANALYSIS OF STEEL BOX GIRDER INSTALLATION USING HIRARC METHOD: (Case Study: Aloha Sidoarjo Flyover Construction Project) - Az Zahra, Karunia; Oetomo, Wateno; Sajiyo, Sajiyo (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2024)
Research on the Aloha flyover construction project aims to determine the risks that occur in the workmanship of installing steel box girder, knowing the level of risk that occurs in the workmanship of installing steel box girder and knowing how to control the risks that occur in the workmanship of installing steel box girder. The method used in this research is the Hazard Identification Risk Assessment and Risk Control (HIRARC) method guided by the Malaysia HIRARC Guidelines (2008). Starting from identifying hazards at each stage of the work activity, a risk assessment is carried out, the results of which can be used as a reference for risk control, so as to reduce the risk of work accidents. The results of the analysis from the identification of hazards and risks arising in 5 stages of work and a total of 11 potential hazard findings were obtained. (1) Preparation stage for steel box girder erection maneuver; (2) The process of leveling/compacting the erection area soil for preparation of crawler crane footing/foundation; (3) The process of mobilizing steel box girder material from stockyard to erection area; (4) Installing slings + seals that will be used during steel box girder erection; (5) The process of installing steel box girder using crawler crane.